ANALISIS KEPUASAN PASIEN TERHADAP MUTU PELAYANAN DI TPPRJ DI RUMAH SAKIT BHAKTI WIRA TAMTAMA SEMARANG PERIODE TAHUN 2011 - Hary Setiadi; Zaenal Sugiyanto (Dian Nuswantoro Semarang, 2012)
Background. Place of registration of outpatients is often regarded as a place of registration, even though this is the place of first contact occurs between patients with officers as thebeginning of a ministry. TPPRJ need to be placed on the officer who has a good competency, security services, as well as providing comfort and enjoyment. therefore, researchers wanted to find out patient satisfaction for the quality of service at the TPPRJ about competence officers, security services, as well as the comfort and enjoyment in the hospital.Method. Type of research used is descriptive, with a survey method and study population were patients who enroll in TPPRJ in 2011 with a sample of 98 patients. This research instrumentusing quisioner with interviews, primary data obtained from quisioner, processed and analyzed descriptively.Result. Results obtained from the research results on aspects of staff competence highest patient satisfaction in terms of officer performance is 92.85%, on the security aspects of patient care the highest satisfaction in terms of security of injury does not occur at the registration counter is equal to 97.95%,on the aspect of comfort and enjoyment of the highest patient satisfaction of service in terms of state of the waiting room in the registration that is equal to 89.79%Conclusion. Of patient opinion about what caused the dissatisfaction of patients in the tpprj then the suggestion that the authors give is more nimble workers in providing care for patients, the TPPRJ more concerned about the ease and speed of service procedures, as well as on the tpprj attention to patient safety while queuing at the counter registrationKey words: patient satisfaction, quality of service, TPPRJ.